A Modified RSA Algorithm for Hiding Text in Colored Images with Random Pixel Selection - A. Naji, Sinan; N. Mohaisen, Hatem; H. Omran, Salman (Opción, 2019)
This study introduces a combination of two techniques: a modified RSA cryp- tography and image-based steganography to improve the overall system’s security level. The system comprises three main steps: message encryption, random traversing path generation, and image-based steganography. We pro- pose to use the addition of factor F along with standard RSA to the make the cryptanalysis task more difficult. Furthermore, LSB image-based steganog- raphy technique is used for hiding the message. However, hiding data on a systematic basis subjects the algorithm to many steganalysis techniques. As a result, the attacker is capable of detecting the inclusion of a secret message within the image. As such, it is important to have an additional level of securi- ty to enhance the protection of the data. This study proposes to use of random pixel selection. For brute-force attack, the attacker not only needs to find the pixels holding the secret bits, but also must determine the appropriate combi- nation of bits in order to reconstruct the hidden data. Compared to standard RSA and LSB techniques, the proposed system achieves a significant security improvement with high image quality.